The relationship between career development, performance appraisal and human resource planning with the organizational succession planning / Nur Izzati Jamaludin - Jamaludin, Nur Izzati (2019)
One of the important activities of the organization in order to achieve the desired objective is through the implementation of Succession Planning. This is because the future performance of the organization depends on the successful implementation of succession planning practice. However, there are many organizations still have a problem with succession planning practice. Succession planning is a systematic process taken by the organization to ensure the continued supply of suitable employees for the replacement of a successor especially for key position in the organization. Having a right employee in the right place at the right time is important to ensure a continued excellence performance of an organization. The aim of this study is to determine the relationship between Career Development, Performance Appraisal and Human Resource Planning with the Organizational Succession Planning. The specific objective of this study is to examine the relationship of Career Development, Performance Appraisal and Human Resource Planning with Petaling Jaya City Council’s Organizational Succession Planning. The study used descriptive research design where the questionnaire has been developed. The questionnaires have been tested for reliability and validity. Then, the data collected has been analyzed by using Statistical Package for Social Science (SPSS) software. Based on the finding, it was found that career development has no significant relationship with organizational succession planning while performance appraisal and human resources planning has a positive significant relationship with organizational succession planning. From the finding, it also found that performance appraisal is the most significant factors that influence organizational succession planning at Petaling Jaya City Council. Finally, several recommendations were provided for Petaling Jaya City Council as a way to make them be more effective in implementing a succession planning practice.